Spatial distribution of the standardized precipitation index in the State of Pará in a decade (Research, Society and Development, 2021)
The distribution of rain is fundamental for the correct planning, at the governmental level, of strategies against natural disasters, water supply, energy generation and waterway transport, and at the production level, as it is important to manage activities that depend on the rain cycle . Aiming to know the reality of the state of Pará, the Standardized Rainfall Index was applied, between the years 2005 to 2015, in a semiannual series, to visualize the behavior of droughts. The data were obtained from the Giovanni platform, from NASA, and, after being processed and plotted by the Panoply application, they were spatialized in QGIS. The results showed a more evident concentration of moisture in the south and west of the state, which was corroborated by data from the National Institute of Meteorology. Finally, the use of the Standardized Precipitation Index proved to be adequate for semiannual observations of moisture distribution for Pará.